(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
ABSTRACTA humidification-dehumidification (HDH) desalination system integrated with flat plate collector (FPC) was investigated experimentally in an attempt to study the production of fresh water using renewable energy. Two types of solar collectors; concentrated parabolic trough solar collector (to heat oil) and non-concentrated (FPC) (to heat saline water before entering the humidifier) were used in this work. Photovoltaic panels (PV) with DC to AC inverter are used to operate, air fan, oil pump and water pumps. The experiments were carried out in August 2016 under climatological conditions of Baghdad- Iraq (latitude 33.33° N, of longitude 44.4° E). Performance of the HDH system is examined with and without FPC. Saline water was first filtered by a sand filter to reduce water turbidity by (85% – 90%) and is also working to eliminate lichens and the suspended solids from saline water. This filtered saline water was processed through humidification dehumidification system based on solar collector for heat source. Selected water samples are tested for Total Dissolved Salt (TDS) in (mg/l), pH, turbidity in (NTU) and electrical conductivity in (?s/cm) measured before and after desalination process. Before filter the water Turbidity is about (11.2 NTU) while after sand filter it is decreased to (1.94 NTU) and it was (0.1 NTU) after dehumidifier. Results showed that the accumulated productivity is (1050 milliliter); it has been improved by 62%when using FPC.